2018
DOI: 10.1039/c8sc03907k
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature magnetic blocking and magneto-structural correlations in a series of dysprosium(iii) metallocenium single-molecule magnets

Abstract: Subtle changes in ligand substitution result in substantial changes in molecular structure and magnetic properties in a series of dysprosium(iii) metallocenium salts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
242
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(284 citation statements)
references
References 65 publications
8
242
1
Order By: Relevance
“…Single‐molecule magnets (SMMs) are molecules that show slow relaxation of magnetisation, and because of this behaviour, they have long been proposed as the ultimate high‐density magnetic storage media . Until recently, this had seemed to be a slightly fanciful proposition, but SMMs based on lanthanide ions, particularly dysprosium(III), have shown barriers for thermal relaxation of magnetisation ( U eff ) approaching 1500 cm −1 , and a magnetic hysteresis has been seen at 60 K and even higher temperatures . These breakthroughs have changed the field of SMMs and yet there is still a limited understanding of the physics that underpins the relaxation of magnetisation in these species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single‐molecule magnets (SMMs) are molecules that show slow relaxation of magnetisation, and because of this behaviour, they have long been proposed as the ultimate high‐density magnetic storage media . Until recently, this had seemed to be a slightly fanciful proposition, but SMMs based on lanthanide ions, particularly dysprosium(III), have shown barriers for thermal relaxation of magnetisation ( U eff ) approaching 1500 cm −1 , and a magnetic hysteresis has been seen at 60 K and even higher temperatures . These breakthroughs have changed the field of SMMs and yet there is still a limited understanding of the physics that underpins the relaxation of magnetisation in these species.…”
Section: Introductionmentioning
confidence: 99%
“…In polymetallic 3 d‐block SMMs, the value of U eff is typically <100 cm −1 , but the Orbach process usually controls relaxation at almost all temperatures . For lanthanide SMMs, and in some pseudo‐linear 3 d‐metal compounds, U eff is much larger, and the Raman term becomes important at lower temperatures . Recently, it has been shown that there is a correlation between the temperature at which magnetisation is retained, often called the blocking temperature, and the relaxation time at the point where the Raman process takes over from the Orbach process …”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that the hysteretic behavior can be reinforced by minimizing underbarrier relaxation pathways and engineering the coupling between the vibrational modes of the ligands and the magnetic states of the core [13][14][15]. Combining these approaches has enabled hysteresis up to unprecedented temperatures of 72 [16] and 80 K [17].…”
mentioning
confidence: 99%
“…The control of the magnetic anisotropy is driven by the nature and the position of the ligands around the metal center. Thus, recently, the use of cyclopentadienyl-based ligands has allowed for the design of mononuclear lanthanide SMMs with a high blocking temperature [20][21][22][23]. These two research fields highlight the important role of the organic ligands associated to the lanthanide ion.…”
Section: Introductionmentioning
confidence: 99%